Microbial Profile of Chronic Suppurative Otitis Media in Patients Attending a Tertiary Care Hospital - Dr. T. Arul Dhivya; Dr. S. Vanathi; Dr. V. Senthilkumar; Dr. S. Swarna (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a persistent infection of the middle ear and mastoid cavity, characterized by ear discharge through a perforated tympanic membrane. It remains a major cause of hearing loss, particularly in developing countries. Materials and Methods: This cross-sectional observational study was conducted over two years in the Department of Microbiology, Veer Surendra Sai Institute of Medical Sciences & Research, Odisha, India, involving 202 patients clinically diagnosed with CSOM. Aural swabs were collected aseptically and processed for bacterial and fungal cultures. Bacterial isolates were identified by standard biochemical methods, and antimicrobial susceptibility was tested using the Kirby-Bauer disk diffusion method according to CLSI guidelines. Fungal isolates were identified by macroscopic and microscopic characteristics. Results: Out of 202 samples, 182 (90.09%) showed microbial growth; 140 (76.92%) were monomicrobial, and 42 (23.07%) were polymicrobial. Among 165 bacterial isolates, Staphylococcus aureus (32.72%) was the most common, followed by Pseudomonas spp. (28.48%), E. coli (11%), and Klebsiella pneumoniae (9.09%). Among 59 fungal isolates, Candida albicans (60%) was predominant, followed by Aspergillus niger (52.17%) and A. flavus (39.13%). All Gram-positive isolates were 100% sensitive to Vancomycin and Linezolid, while Gram-negative isolates showed highest sensitivity to Gentamicin (93.61%), Amikacin, Imipenem, and Meropenem (85.10% each). Resistance to cephalosporins and amoxicillin-clavulanic acid was noted. Conclusion: CSOM continues to be a polymicrobial infection dominated by Staphylococcus aureus and Pseudomonas spp. Emergence of multidrug resistance, particularly to cephalosporins and β-lactam/β-lactamase inhibitors, necessitates culture-based antibiotic therapy. Ciprofloxacin and aminoglycosides remain effective options, although caution is advised due to ototoxicity risk.